Structural, electrical and magnetic properties of eco-friendly complex multiferroic material: Bi(Co0.35Ti0.35Fe0.30)O3. Issue 1 (January 2019) - Kumar, Nitin; Shukla, Alok; Kumar, Nripesh; Choudhary, R.N.P.
Abstract: In this communication, studies of basic crystal structure, microstructure, dielectrics, impedance, conductivity, electric polarization and magnetization of an eco-friendly distorted perovskite Bi(Co0.35 Ti0.35 Fe0.30 )O3 (abbreviate as BCTF70/30) have been reported. Analysis of crystal structure, phase formation and composition of the specimen, carried out through the powder X-ray diffraction (XRD) and energy dispersive X-ray spectroscopy (EDXS) techniques, confirms the formation of single-phase orthorhombic system at room temperature. The surface morphology of the compound, evaluated through the field emission scanning electron microscope, displayed the formation of high-density sample with uniform distributions of grains of varying dimensions. The phonon mode, intensity, location and width of the Raman peaks were analyzed using the Raman spectroscopy. The correlation between the frequency-temperature dielectric parameters, impedance parameters and electrical conductivity with structure-microstructure has been established. The influence of grain and grain boundary on the resistive and capacitive features has been examined through impedance spectroscopy formalism with an idealized simulated circuit. Studies of impedance spectroscopic show the semiconductor nature (i.e., negative temperature coefficient of resistance) and the non-Debye type relaxation. Polarization versus electric field analysis of BCTF70/30 sample displays enhanced value of remnant polarization as compared to that of BFO. The magnetic hysteresis loop analysis also exhibits significant improvement in the magnetization values of the compound. Accordingly, based on such enhancement of remnant polarization and magnetic parameters, we assumed that an eco-friendly material of BCTF70/30 could considered as promising material for some new electronic devices.